Labor supply reaction to wage cuts and tax increases: Areal-effort experiment - Tomoharu Mori; Hirofumi Kurokawa; Fumio Ohtake (Osaka University, Institute of Social and Economic Research (ISER), 2020)
We investigate the labor supply reaction to wage cuts and tax increases using a real-effort experiment. First, subjects perform a task and receive a reward with taxes deducted. Second, the wage cut treatment reduces the wage rate and the tax increase treatment increases the tax; wage and tax remain unchanged for the control group. The real wage is equal for both treatments, and both treatments had significantly smaller increases in effort levels than the control group. The effort level change did not differ between the treatments. Therefore, the net wage illusion and tax aversion identified in previous studies are absent.
Keywords: C91; H24; J24; 330; labor supply; net wage illusion; tax aversion